Faktor Faktor yang Berhubungan dengan Kadar Hemoglobin pada Ibu Hamil di Wilayah Kerja Puskesmas Mopuya - Sanjaya, Gusti D.; Mayulu, Nelly; Kawengian, Shirley E.S. (eBiomedik, 2018)
Abtract: Iron deficiency anemia remains as a public health problem with respect to its high prevalence and impact on maternal and infant health. This type of anemia often occurs because in pregnant women there is an increase in iron demand doubled due to increased plasma volume. This study was aimed to determine the relationship between hemoglobin level and maternal age, gestational age, parity, gestational distance, MUAC size, mother jobs, mother education, family income, and eating patterns. This was an analytical descriptive study with a cross-sectional design conducted at Mopuya Community Health Center, Bolaang Mongondow. Total respondents were 66 pregnant women obtained by using total sampling method. The relationship of hemoglobin level and the variables obtained the P-values as follows: 0.000 for mother age; 0,000 for pregnancy age; 0.000 for parity; 0.01 for pregnancy distance; 0.01 for MUAC; 0.01 for job status; 0.000 for mother education; 0.000 for family income; 0.000 for nuts diet; 0.000 for meat diet; 0.87 for fish diet; 0.000 for egg diet; all P-values were less than Î±=0.05, except fish diet that had a P-value higher than Î±=0.05. Conclusion: There were significant relationships between hemoglobin level and maternal age, gestational age, parity, pregnancy distance, LILA size, mother job, mother education, family income, as well as consumption pattern of eating nuts, meat, and eggs. However, there was no relationship between hemoglobin level and fish diet.Keywords: hemoglobin, anemia, pregnant motherÂ Abstrak: Anemia defisiensi besi masih menjadi masalah kesehatan masyarakat sehubungan dengan prevalensinya yang tinggi dan dampak kesehatan terhadap ibu dan bayinya. Anemia jenis tersebut sering terjadi karena pada ibu hamil terjadi peningkatan kebutuhan zat besi dua kali lipat akibat peningkatan volume plasma. Penelitian ini bertujuan untuk mengetahui adanya hubungan antara usia ibu hamil, usia kehamilan, paritas, jarak kehamilan, ukuran LILA, status pekerjaan ibu, pendidikan ibu, pendapatan keluarga, dan pola konsumsi makan dengan kadar hemoglobin (Hb). Jenis penelitian ialah analitik deskriptif dengan desain potong lintang, yang dilakukan di Puskesmas Mopuya Kecamatan Bolaang Mongondow. Terdapat total 66 responden, diperoleh dengan metode total sampling. Hasil penelitian mendapatkan nilai P sebagai berikut: 0,000 untuk usia ibu; 0,000 usia kehamilan; 0,000 paritas; 0,01 jarak kehamilan; 0,01 LILA; 0,00 status pekerjaan; 0,000 pendidikan; 0,000 pendapatan; 0,000 pola makan kacang-kacangan; 0,000 pola makan daging; 0,87 pola makan ikan; 0,000 pola makan telur; kesemuanya lebih kecil dibandingkan Î±=0,05 kecuali untuk pola makan ikan dengan nilai P lebih besar Î±=0,05. Simpulan: Terdapat hubungan bermakna antara kadar hemoglobin (Hb) dengan usia ibu, usia kehamilan, paritas, jarak kehamilan, ukuran LILA, status pekerjaan, pendidikan ibu, pendapatan keluarga, pola konsumsi makan kacang-kacangan, daging dan telur. Tidak terdapat hubungan antara kadar hemoglobin dengan pola makan ikan.Kata kunci: kadar hemoglobin (Hb), anemia, ibu hamil